Antibiotics at the crossroads - Do we have any therapeutic alternatives to control the emergence and spread of antimicrobial resistance? - Mohan Bilikallahalli Sannathimmappa; Vinod Nambiar; Rajeev Aravindakshan (Wolters Kluwer Medknow Publications, 2021)
Antibiotics once regarded as magic bullets are no more considered so. Overuse of antibiotics in humans, agriculture, and animal husbandry has resulted in the emergence of a wide range of multidrug-resistant (MDR) pathogens which are difficult to treat. Antimicrobial resistance (AMR) is a serious global health problem associated with high mortality in the era of modern medicine. Moreover, in the absence of an effective antibiotic, medical and surgical interventions can highly become a risk. In recent times, the decreased incline of pharmaceutical industries toward research and development of newer effective antibiotics to fight this MDR pathogens have further fuelled the scarcity of antibiotics, thus the number of antibiotics in the pipeline is extremely limited. Hence it is high time for the development of new strategies to fight against dangerous MDR pathogens. Currently, several novel approaches explored by scientists have shown promising results pertaining to their antimicrobial activity against pathogens. In this article, the authors have summarized various novel therapeutic options explored to contain AMR with special attention to the mechanism of action, advantages, and disadvantages of different approaches.